Maternal autonomy and the education of the subsequent generation: Evidence from three contrasting states in India - Marco Alfano; Wiji Arulampalam; Uma Kambhampati (Institute for the Study of Labor (IZA), 2011)
This paper makes a significant contribution on both conceptual and methodological fronts, in the analysis of the effect of maternal autonomy on school enrolment age of children in India. The school entry age is modelled using a discrete time duration model where maternal autonomy is entered as a latent characteristic, and allowed to be associated with various parental and household characteristics which also conditionally affect school entry age. The model identification is achieved by using proxy measures collected in the third round of the National Family Health Survey of India, on information relating to the economic, decision-making, physical and emotional autonomy of a woman. We concentrate on three very different states in India - Andhra Pradesh, Kerala and Uttar Pradesh. Our results indicate that female autonomy is not associated with socio-economic characteristics of the woman or her family in Kerala (except maternal education), while it is strongly correlated to these characteristics in both Andhra Pradesh and Uttar Pradesh. Secondly, while female autonomy is significant in influencing the school starting age in UP, it is less important in AP and not significant at all in Kerala.
urn:nbn:de:101:1-201110263576
Keywords: I2; J12; C35; 330; latent factor models; structural equation models; female autonomy; school enrolment decisions; India; National Family Health Survey; Mütter; Autonomie; Schulbesuch; Kinder; Altersgruppe; Indien